2016
DOI: 10.1007/s10295-016-1767-1
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Sludge Biotic Index (SBI), Sludge Index (SI) and filamentous bacteria analysis for assessing activated sludge process performance: the case of piggery slaughterhouse wastewater

Abstract: Piggery slaughterhouse wastewater poses serious issues in terms of disposal feasibility and environmental impact, due to its huge organic load and variability. It is commonly treated by means of activated sludge processes, whose performance, in case of municipal wastewater, can be monitored by means of specific analyses, such as Sludge Biotic Index (SBI), Sludge Index (SI) and floc and filamentous bacteria observation. Therefore, this paper was aimed at assessing the applicability of these techniques to pigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Almost all the biological processes have been explored in terms of biomass composition (bacteria, protozoa, metazoan, and fungi) and activity: conventional activated sludge, attached biomass, membrane reactors, and treating either municipal [27][28][29][30][31][32][33][34] or industrial wastewater [35][36][37][38][39]. Likewise, identification and quantification of microorganisms operating under different conditions (aerobic, anoxic, and anaerobic) have been reported [25,[40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all the biological processes have been explored in terms of biomass composition (bacteria, protozoa, metazoan, and fungi) and activity: conventional activated sludge, attached biomass, membrane reactors, and treating either municipal [27][28][29][30][31][32][33][34] or industrial wastewater [35][36][37][38][39]. Likewise, identification and quantification of microorganisms operating under different conditions (aerobic, anoxic, and anaerobic) have been reported [25,[40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient and organic matter removal processes carried out in the activated sludge are based on the activity of the studied microorganisms, thus maintaining optimal conditions for their growth and development is necessary for a better process control and management 18 . The dynamics and organization of microbial communities, along with biotic components of the activated sludge, determine its quality and the efficiency of the depuration process 16 .…”
Section: Discussionmentioning
confidence: 99%
“…WWTP performance should guarantee a certain effluent quality which will vary according to the posterior uses of water. Different techniques have been developed to measure activated sludge quality, such as Sludge Biotic Index (based on the presence and abundance of certain protists) or the Sludge Index (considering macroscopic and microscopic activated sludge features) [16][17][18] . A complementary tool to control microbial community and activated sludge stability based on the bacterial populations is necessary to assess WWTP performance and prevent activated sludge disruptions.…”
mentioning
confidence: 99%
“…This indicator has even been applied for researching slaughterhouse wastewater treatment [32]. The authors have identified SBI as a very useful indicator for determining both the condition of activated sludge and the analysis of biological working conditions of treatment plants.…”
Section: Discussionmentioning
confidence: 99%